2016
DOI: 10.1136/annrheumdis-2016-209589
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting expression pattern of RNA-sensing receptors TLR7, RIG-I and MDA5 in interferon-positive and interferon-negative patients with primary Sjögren's syndrome

Abstract: Here we conclude a contrasting expression pattern of the RNA-sensing receptors TLR7, RIG-I and MDA5 in pDCs and monocytes of patients with IFNpos pSS. This profile could explain the pathogenic IFN production and might reveal novel therapeutic targets in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 51 publications
(50 reference statements)
6
69
1
1
Order By: Relevance
“…Zheng et al reported that TLR-7 and TLR-9 were predominantly expressed in lymphocytes of the parotid glands from pSS patients compared to those of control subjects [6]. In contrast, Maria et al reported that TLR-7 was expressed by few cells within the lymphocytic foci [16]. Our present findings demonstrate that TLR-7 was expressed more strongly than TLR-9 in mononuclear cells of labial salivary glands.…”
Section: Discussioncontrasting
confidence: 51%
See 2 more Smart Citations
“…Zheng et al reported that TLR-7 and TLR-9 were predominantly expressed in lymphocytes of the parotid glands from pSS patients compared to those of control subjects [6]. In contrast, Maria et al reported that TLR-7 was expressed by few cells within the lymphocytic foci [16]. Our present findings demonstrate that TLR-7 was expressed more strongly than TLR-9 in mononuclear cells of labial salivary glands.…”
Section: Discussioncontrasting
confidence: 51%
“…However, the expression of TLR-7-9 in salivary glands has not been well investigated. In contrast, Maria et al reported that TLR-7 was expressed by few cells within the lymphocytic foci [16]. In contrast, Maria et al reported that TLR-7 was expressed by few cells within the lymphocytic foci [16].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…A recent examination of the relationship between type I IFN and pDCs in SS conducted a genome-wide microarray analysis of isolated pDCs and CD14 + monocytes obtained from 115 patients with pSS and 42 healthy subjects [109]. In accordance with the above-cited studies, TLR7 gene (but not TLR9 gene) was up-regulated when the cell types were restricted to IFN-positive cells.…”
Section: The Involvement Of Tlrs In Sjögren’s Syndromementioning
confidence: 96%
“…However, B cells from pSS patients secrete increased amounts of several pro-inflammatory cytokines when stimulated with agonists for TLR7 or TLR9, suggesting that TLR signaling in B cells may contribute to the chronic inflammatory landscape observed [106]. Interestingly, a recent study found that when pSS patients were segregated on the basis of type I IFN expression, pDCs and monocytes from the IFN-expressing subset expressed elevated levels of TLR7, whereas IFN negative patients expressed normal levels of TLR7 [107]. Thus, these studies suggest that endosomal TLRs contribute to SS and may be particularly important in IFN positive patients, although further work is required to understand the way in which TLR signaling pathways mediate pathology in SS.…”
Section: Mechanisms Of Innate Immune Activation In Ssmentioning
confidence: 99%